2016
DOI: 10.1039/c6dt01948j
|View full text |Cite
|
Sign up to set email alerts
|

Controlling uranyl oxo group interactions to group 14 elements using polypyrrolic Schiff-base macrocyclic ligands

Abstract: Heterodinuclear uranyl/group 14 complexes of the aryl- and anthracenyl-linked Schiff-base macrocyclic ligands L and L were synthesised by reaction of UO(HL) with M{N(SiMe)} (M = Ge, Sn, Pb). For complexes of the anthracenyl-linked ligand (L) the group 14 metal sits out of the N-donor plane by up to 0.7 Å resulting in relatively short MOUO distances which decrease down the group; however, the solid state structures and IR spectroscopic analyses suggest little interaction occurs between the oxo and group 14 meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 26 publications
4
31
1
Order By: Relevance
“…The formation of oxo complexes with structures such as UL n vO, [21][22][23] L n UuO 13,24 or U-O-U 25 N-oxide to a metal is not unique, although relatively rare. 13,[26][27][28][29] The solid-state structure reveals a U IV complex with a distorted octahedral geometry with the boroxide ligands in the equatorial positions and the pyridine N-oxide ligands in the axial positions ( Fig. 3).…”
Section: Reactions Of 1 M and 1 Tmentioning
confidence: 99%
“…The formation of oxo complexes with structures such as UL n vO, [21][22][23] L n UuO 13,24 or U-O-U 25 N-oxide to a metal is not unique, although relatively rare. 13,[26][27][28][29] The solid-state structure reveals a U IV complex with a distorted octahedral geometry with the boroxide ligands in the equatorial positions and the pyridine N-oxide ligands in the axial positions ( Fig. 3).…”
Section: Reactions Of 1 M and 1 Tmentioning
confidence: 99%
“…These hydrogen bonds directly weaken the An = O endo and further An = O exo , which makes the An = O stretching frequency of M‐ pyAn VI be regularly lower than the one of B‐ pyAn VI . Recent IR measurement yielded the U = O stretching value of 910 cm −1 for [(thf)(U VI O 2 )(H 2 L)] (M‐ thfU VI ), only slightly redshifting relative to 912 cm −1 for B‐ pyU VI . The experimental redshift, which is not so pronounced as calculated results, may be attributed to the solvent difference between experimentally‐determined M‐ thfU VI and B‐ pyU VI complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous theoretical study suggested that the penta valent uranyl bar is less rigid than the hexa valent one and more easily transformed to the cis ‐structure. Experimentally, Arnold and Love et al have chemically modified the aryl‐linked H 4 L Ar ligand and prepared an anthracenyl‐containing polypyrrolic macrocycle (H 4 L, Chart ) that has longer linker . The enlarged space allows the ligand H 4 L to complexate two trans ‐uranyl(VI) rods .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two seminal, coincident reports of the potassium‐reduced coordination polymer {[UO 2 (py) 5 ][KI 2 (py) 2 ]} ∞ ( A ) showed that anaerobic uranyl(V) complexes are stable against disproportionation; since then, significant advances have been made in isolating uranyl(V) complexes. The reductive oxo functionalization with Group 1, Group 2, d‐block, rare‐earth, actinide, and main‐group metals as well as silicon is also possible. The linearity of the f 1 uranyl also provides a rare opportunity in f‐block chemistry to control the orientation of the magnetic vector, and uranyl(V)/transition‐metal single‐molecule magnets have been made through this oxo‐bridging strategy .…”
Section: Figurementioning
confidence: 99%